N. ULYANOV`S LITERARY-CRITICAL VIEWS - Galina L. Nefagina (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article is devoted to the literary-critical views of the representative of the second wave of Russian emigration N. Ulyanov. Among the generation of emigre writers who received a Soviet education and absorbed the Soviet way of thinking, Ulyanov was an exceptional phenomenon, possessing encyclopedic knowledge of Russian and foreign culture, and most importantly, freedom of thought. His works, published in the collections “Scripts”, “Diptych”, “Descent of the Flag”, make it possible to understand the history and peculiarities of the formation of literature of the second wave of emigration, the specifics of the genre of the historical novel, and crisis phenomena in the culture of the 20th century. The main problems of Ulyanov`s literary-critical work are associated with determining the place of DP writers in the literature of the Russian diaspora and the goals of their work, with the possibility of fulfilling the mission of new emigrants as successors of the spiritual traditions of the first emigration. Ulyanov believed that the fundamental position of the concept of emigre literature was not the fictionalization of political views, but a high aesthetic level. Calling the émigré writers of his generation “children of the sunset,” Ulyanov expressed concern about the fate of not only Russian literature, but also European culture, in which the beautiful is beginning to be replaced by the ugly, and beauty by utilitarianism. The analysis of Ulyanov’s literary-critical articles expands the space of knowledge about the literature of the second wave of emigration. All Ulyanov’s works on literature revolve around basic and fundamentally important theses: literary fiction as a necessary condition for its development and the ruin of a culture devoid of the beautiful and spiritual. From these fundamental problems arise his reflections on the DP writers, on their role as successors of the literature of the first wave of emigration, the rejection of political engagement in literature and the anticipation of the death of culture. Written by brilliant style, impeccable language, demonstrating encyclopedic erudition of the author N. Ulyanov’s articles reflect the main problems of formation of literature and criticism of the second wave of emigration and present valuable material for researchers.